JWST/NIRCam 4–5 μm Imaging of the Giant Planet AF Lep b - Kyle Franson; William O. Balmer; Brendan P. Bowler; Laurent Pueyo; Yifan Zhou; Emily Rickman; Zhoujian Zhang; Sagnick Mukherjee; Tim D. Pearce; Daniella C. Bardalez Gagliuffi; Lauren I. Biddle; Timothy D. Brandt; et al. (The Astrophysical Journal Letters)
With a dynamical mass of 3 M _Jup , the recently discovered giant planet AF Lep b is the lowest-mass imaged planet with a direct mass measurement. Its youth and spectral type near the L/T transition make it a promising target to study the impact of clouds and atmospheric chemistry at low surface gravities. In this work, we present JWST/NIRCam imaging of AF Lep b. Across two epochs, we detect AF Lep b in F444W (4.4 μ m) with signal-to-noise ratios of 9.6 and 8.7, respectively. At the planet’s separation of 320 mas during the observations, the coronagraphic throughput is ≈7%, demonstrating that NIRCam’s excellent sensitivity persists down to small separations. The F444W photometry of AF Lep b affirms the presence of disequilibrium carbon chemistry and enhanced atmospheric metallicity. These observations also place deep limits on wider-separation planets in the system, ruling out 1.1 M _Jup planets beyond 15.6 au (0.″58), 1.1 M _Sat planets beyond 27 au (1″), and 2.8 M _Nep planets beyond 67 au (2.″5). We also present new Keck/NIRC2 $L^{′} $ imaging of AF Lep b; combining this with the two epochs of F444W photometry and previous Keck $L^{′} $ photometry provides limits on the long-term 3–5 μ m variability of AF Lep b on timescales of months to years. AF Lep b is the closest-separation planet imaged with JWST to date, demonstrating that planets can be recovered well inside the nominal (50% throughput) NIRCam coronagraph inner working angle.